Toward gene therapy in rheumatoid arthritis. Issue 3 (3rd May 2020) - Young, Emily; Gould, David; Hart, Stephen
ABSTRACT: Introduction: Rheumatoid arthritis (RA) is an autoimmune disease of the joint, affecting 0.24% of the global population. Many patients only respond partially or not at all to current therapies while the systemic complications of immunosuppression associated with these treatments are unacceptable. Genetic therapies for RA have the potential to improve treatments by targeting delivery to the disease site, enhancing efficacy, and avoiding adverse effects. Areas covered: The route of administration, delivery vector, nucleic acid type, and target gene must be carefully selected to develop an effective RA gene therapy. Drawing from examples of RA gene therapies investigated in animal models and clinical trials, this review discusses how these strategies may be used to translate RA gene therapy into the clinic. Expert opinion: Existing RA treatments lack specificity to the joint. Genetic delivery systems can include targeting properties, such as disease-responsive promoters or cell-targeting moieties, to overcome this. Non-viral vectors, in particular, can be engineered easily to possess these properties and, unlike viral vectors, display low immunogenicity. Contrary to current drugs, gene therapy can be delivered intra-articularly, providing sustained levels of the therapeutic. Targeted vectors may also achieve this, but with a single systemic injection, simultaneously delivering the therapeutic to all affected joints.